The human long noncoding RNAs CoroMarker, MALAT1, CDR1as, and LINC00460 in whole blood of individuals after controlled short-term exposure with ultrafine metal fume particles at workplace conditions, and in human macrophages in vitro - Theresa Scheurer; Jan Steffens; Agnieszka Markert; Miriam Du Marchie Sarvaas; Christoph Roderburg; Lothar Rink; Frank Tacke; Tom Luedde; Thomas Kraus; Ralf Baumann (Journal of Occupational Medicine and Toxicology)
Abstract Background Short-term inhalation of occupationally relevant ultrafine zinc/copper (Zn/Cu) containing welding fumes has been shown to induce subclinical systemic inflammation, associated with an elevated risk for cardiovascular diseases. The involvement of noncoding RNAs (lncRNAs) in this setting is currently unknown. However, lncRNAs have been reported to fulfill essential roles in, e.g., cardiovascular diseases, inflammation, infectious diseases, and pollution-related lung disorders. Methods In this study, the specific lncRNAs levels of the 4 lncRNAs CoroMarker, MALAT1, CDR1as and LINC00460 were determined by RT-qPCR in THP-1 macrophages exposed to Zn/Cu metal fume suspensions for 1, 2, and 4 hours in vitro. Furthermore, 14 subjects were exposed to Zn/Cu containing welding fumes (at 2.5 mg/m3) for 6 hours. Before, 6, 10, and 29 hours after exposure start, whole blood cell lncRNAs levels were determined by RT-qPCR. Results In THP-1 macrophages, we observed a 2.3-fold increase of CDR1as at 1 h (Wilcoxon p = 0.03), a non-significant increase of CoroMarker at 1 h, and an increase of LINC00460 at 2 h (p = 0.03) and at 4 h (p = 0.06). In whole blood cells, we determined a non-significant upregulation of CDR1as at 6 h (p = 0.2), a significant downregulation of CoroMarker at 6 h (p = 0.04), and a significant upregulation of LINC00460 levels at 10 h (p = 0.04) and 29 h (p = 0.04). MALAT-1 remained unchanged in both settings. Conclusion The orientation of regulation of the lncRNAs is (except for CoroMarker) similar in the in vitro and in vivo experiments and in line with their described functions. Therefore, these results, e.g. the upregulation of the potential risk marker for cardiovascular diseases, CDR1as, contribute to understanding the underlying mechanisms of Zn/Cu-induced subclinical inflammation in metal workers.